HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS RAWAT INAP SIDOMULYO KOTA PEKANBARU - Yulita, Emi; Aldinda, Tharra Widadari; Dilla, Diva Zikri (Ensiklopedia of Journal, 2023)
Nutritional problems are also one of the indirect causes of maternal and child death that can still be prevented. One of the malnutrition problems for pregnant women is anemia, where there is a decrease in the quantity and quality of red blood cells, this is aggravated by the occurrence of the hemodilution process in pregnancy so that hemoglobin levels decrease which has the potential to increase the risk of illness and death of the mother and fetus. This study aims to determine the relationship between nutritional status and the incidence of anemia in pregnant women in the work area of the Sidomulyo Inpatient Health Center in Pekanbaru City. Carried out in the Working Area of the Sidomulyo Inpatient Health Center in Pekanbaru city, which was carried out in April-July 2023 with a sample of 43 respondents. This type of research is quantitative with a cross sectional study design.  The statistical test used is Chi-Square. The results of the analysis showed a p-value of 0.004, meaning that there is a relationship between nutritional status and the incidence of anemia in pregnant women. Efforts to maintain and improve the nutritional status of pregnant women can be done through antenatal counseling and supervision (Antenatal Care), while in the prevention and overcoming anemia it is necessary to supervise the administration of Fe tablets at least 90 tablets and also make a target map of Fe tablets for pregnant women.